Analysis of lossy microwave structures and microstrip resonators by the TLM method - Akhtarzad, Sina (1975)
Many problems in electrical engineering are associated with the way in which electric and magnetic fields propagate and distribute themselves in various media. Maxwell's equations provide a concise description for the interaction of fields with themselves and with the various boundaries of a problem. Therefore, a numerical procedure for the solution of these equations is an important consideration. This thesis shows how a general three-dimensional medium may be represented by an interconnection of continuous ideal two-wire transmission-lines made up of generalised two-dimensional nodes which are introduced in the earlier chapters. It is then shown how this model may be used for the numerical solution of the electric and magnetic vector fields within the medium. This is the TLM method of numerical analysis.